Estudio de prefactibilidad para el montaje de un sistema de franquicias para el restaurante La Spaghettata en Bogotá (2017)
The present document contains the pre-feasibility study for the installation of the franchise system of the restaurant La Spaghettata in Bogotá. It is mainly sought to make the business increase under the franchise mode and take advantage of the boom that this system is currently having in the country and in South America. It is proven that this modality of growth is currently the most effective and the lowest risk of failure, so it is a matter of replicating a successful business. The information collected to carry out this report comes from the restaurant La Spaghettata and another part is obtained from secondary information as Internet sources and specialized magazines.